(untitled) (Research, Society and Development, 2023)
This study looked at how road transport influenced the sale and availability of products from farmers to traders in Rapale district,Nampula Province. The purpose was to determine the impact of road systems on agricultural transportation, production, and marketing in the region. Descriptive statistics and Geographic Information Systems were used to analyze how seasonal variations in weather affected the quantity of products. It was found that roads leading to the villages were more prone to flooding during the rainy season, resulting in fewer products being sold. However, in Rapale-sede, the opposite was observed; even so, the rainy season was more expensive than the dry season, making trucks/minibuses the most cost-effective transportation option for both farmers and traders. Maps were produced depicting the distance between data collection points, main roads, and the Waresta wholesale market, as well as the distances traveled by farmers and traders. It was concluded that improving the roads could lead to an increase in production and commercialization.